Aikuisiällä ADHD-diagnoosin saaneiden naisten hoitopolut ja diagnoosille annetut merkitykset - Haukimäki, Tanja (2024)
In this thesis, I examine the meanings that women diagnosed with ADHD in adulthood attribute to their diagnosis, as well as their experiences of the diagnostic process, comparing these to the Käypä hoito (Current Care) guidelines. I conducted five semi-structured interviews, which I analyzed using thematic analysis. The theoretical framework is based on Claude Levi-Strauss's concept of bricolage combined with agency, particularly drawing on the theories of Marja-Liisa Honkasalo and Sherry B. Ortner. Additionally, I employed a narrative approach, emphasizing the importance of experience and interpretative reading in this study.